Kebijakan Ekonomi Sultan Agung dan Transformasi Perekonomian Kesultanan Mataram Islam Tahun 1613-1645 M - Oktavian Priyo Legowo; Miftakhur Rochmah; Muhammad Sabilur Rosyad (Dampeng: Journal of Art, Heritage and Culture, 2026)
Studies on Sultan Agung Hanyokrokusumo have predominantly emphasized political, military, and territorial expansion, while his economic policies have received comparatively limited scholarly attention. This study examines the contribution of Sultan Agung’s economic policies in agriculture, trade, and taxation to the economic transformation of the Islamic Mataram Sultanate during 1613–1645. This historical research employs the historical method, including heuristic source collection, source criticism, interpretation, and historiography. Data were collected through library research using Javanese babad (chronicles), Dutch East India Company (VOC) archives, and relevant academic literature, and were analyzed using historical and descriptive-analytical approaches. The findings indicate that agricultural intensification, strengthened trade networks, and a centralized taxation system reinforced food security, state revenue, and regional economic integration. The novelty of this study lies in analyzing these three sectors as an integrated economic strategy that strengthened Sultan Agung’s rule. Further research is recommended to examine the socio-economic impacts of these policies at the local level using more diverse historical sources. [Kajian mengenai Sultan Agung Hanyokrokusumo selama ini lebih banyak menitikberatkan pada aspek politik, militer, dan ekspansi wilayah, sedangkan kebijakan ekonominya masih relatif kurang mendapat perhatian. Penelitian ini bertujuan menganalisis kontribusi kebijakan ekonomi Sultan Agung di bidang pertanian, perdagangan, dan perpajakan terhadap transformasi ekonomi Kesultanan Mataram Islam pada periode 1613–1645. Penelitian ini menggunakan metode sejarah yang meliputi heuristik, kritik sumber, interpretasi, dan historiografi. Data diperoleh melalui studi pustaka dengan memanfaatkan babad Jawa, arsip VOC, dan berbagai literatur ilmiah, kemudian dianalisis secara historis dan deskriptif-analitis. Hasil penelitian menunjukkan bahwa intensifikasi pertanian, penguatan jaringan perdagangan, dan sistem perpajakan yang terpusat mampu memperkuat ketahanan pangan, pendapatan negara, dan integrasi ekonomi antardaerah. Kebaruan penelitian ini terletak pada analisis ketiga sektor tersebut sebagai satu strategi ekonomi yang terpadu dalam memperkuat kekuasaan Sultan Agung. Penelitian ini merekomendasikan kajian lanjutan mengenai dampak sosial-ekonomi kebijakan tersebut pada tingkat lokal dengan memanfaatkan sumber sejarah yang lebih beragam.]